Review of Agricultural Waste Utilization as Improvement Additives for Residual Tropical Soils - Ishola, K.; Olawuyi, O. A.; Bello, A. A.; Etim, R. K.; Yohanna, P.; Sani, J. E. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
The development of a nation partially depends on sustainable materials obtained from agricultural products. Increased agricultural products could increase the amount of waste generated yearly. This paper presents a review on the use of agricultural waste with pozzolanic properties (rice husk ash, Locust bean waste ash, Palm oil fuel ash, Banana leaf ash, Bagasse ash, Coconut shell ash, Bamboo leaf ash, Corn cob ash, Cassava peel ash and Palm kernel shell ash) in various geotechnical engineering applications. Interestingly, these wastes were subjected to various laboratory tests such as (particle size distribution, Compaction, Atterberg, unconfined compressive strength (UCS) and California bearing ratio (CBR)) to assess their effectiveness in soil improvement. In all these, the percentages of the materials required for soil improvement were discussed. The reports from various researchers have shown that agricultural waste having pozzolanic properties improves the engineering properties of soil. For instance, palm oil fuel ash (POFA) is mostly used as an admixture in concrete as reported elsewhere. Few studies have been carried out on the use of banana leaf ash and palm oil fuel ash as soil improvement materials. It is recommended that further researches should focus on the possibility of using other agricultural waste from Cocoyam, Yam peel, maize trunk, Cashew and Guava that have limited reporting researches for use as soil improvement materials.